Effect of shortening close-up period length with or without lasalocid supplementation on production performance of dairy cows - ATRIAN, PEJMAN; AMANLOU, HAMID; MAHERI-SIS, NASER; SHAHRYAR, HABIB AGHDAM (The Indian Journal of Animal Sciences, 2019)
To determine the effect of shortening the close-up period length with or without lasalocid supplementation on dry matter intake (DMI) as well as milk production and composition, 48 dry Holstein cows with 700±50 kg live body weight, 3-5 years old and BCS=3.75±0.25, in 210 days of pregnancy, were used. The experiment was planned as a completely randomized design with a 4 × 12 arrangement of treatments. Control group cows (21-L) had 21 days close-up dry period without lasalocid, second group (21+L) had 21 day close-up with lasalocid, third group (10-L) had shortened close-up dry period without lasalocid and last group (10+L) had shortened close-up period associated with lasalocid. The experiment started from inception of dry period and finished at the end of 42 days in milk (DIM). Results showed that although shortening of the period length associated with the use of lasalocid, could not alter prepartum DMI, but significantly increased postpartum DMI and milk production, improved feed conversion ratio (FCR), and decreased milk fat and protein content. Hence, shortening of close-up period from 21 days to 10 days associated with lasalocid supplementation resulted in better productivity of dairy cows.